Implementation of PLTS as a Lighting System for the Waetuo Fishermen's Group Chart, Pinrang Regency as an Effort to Improve the Economy of Coastal Communities - Muslimin, Zaenab; Mayasari, Fitriyanti; Irwan, Irninthya Nanda Pratami; Amir, Ashadi; faraby, Muhira Dzar; Usman, Usman; Idris, Ahmad Rosyid (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
The Wae Tuoe Fishermen Group in Pinrang Regency is a coastal community located in Suppa District, Pinrang Regency, South Sulawesi Province, where the majority of the population relies on marine resources for their livelihood. The bagang is a structure made of wood or bamboo located in the middle of the sea, about 500 meters to 2 kilometers from the shore, used by fishermen to catch or store fish. The bagang has great potential but is not optimally utilized by fishermen as a source of livelihood and economic improvement. This is because the fish catch is maximized at night. The limited lighting, which could help optimize the fishing process, is due to the restricted availability of electricity from generators. The development of solar cell technology, which can generate and store electricity, is a new breakthrough in the use of renewable energy. The use of solar cells is expected to provide an energy source for lighting on the bagang, allowing fishermen to maximize their activities at night. The solar cell lighting system is designed to supply six light points with a capacity of 5 x 50 watts operating at night from 7:00 PM to 4:00 AM. The design of the PLTS, which consists of two solar panels with a capacity of 550 Wp, four 12 V batteries with a capacity of 100 Ah, and a 1000-watt inverter, is expected to provide electricity as a lighting source for the bagang during the night. After conducting counseling and training on solar power plant (PLTS) technology, 18 out of 20 members of the Wae Tuoe Fishermen Group gained knowledge about the utilization, design, installation process, usage, and maintenance of PLTS technology.